INVESTMENT OPPORTUNITIES AND PROSPECTS IN THE KASHKADARYA REGION - Rakhxmonova, Durdona Xasan kizi (THE INNOVATION ECONOMY, 2026)
This article provides an in-depth scientific analysis of the investment attraction opportunities and prospects for regional economic development in the Kashkadarya region, one of the areas with the largest economic potential in the Republic of Uzbekistan. The main objective of the study is to evaluate the existing investment climate in the region, identify structural changes in the sectoral distribution of capital investments, and develop strategic directions aimed at diversifying and reducing the resource dependence of the regional economy through innovation. The article examines the dynamics of macroeconomic and investment indicators for the еars 2021–2025 using statistical, econometric, and comparative analysis methods. The results indicate that while the volume of foreign direct investment is increasing, the majority of it is still directed towards the energy and extractive sectors. In the discussion section, scientifically grounded practical proposals and recommendations are developed to mitigate the risk of the “resource curse,” develop industrial clusters, and expand investments in human capital and green energy.